Colour Visual Cryptography (3,3) Scheme - et. al., Mandru Manisha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Visual Cryptography is an encryption technique which performs only encryption in cryptography, and it is used to encrypt every visual data. And this cryptography is different and unique in all cryptographic techniques, because of not performing decryption process mechanically, and that is done mechanically. In normal visual cryptography only black and white images are encrypted. In this paper we propose a different type of visual cryptography scheme for colour imagesin CMY format. And it protects the secret of the original image and no other techniques does not decrypt it except our decryption technique.